PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KOMITMEN DAN KINERJA RELAWAN PADA RADIO KOMUNITAS DI TIMOR-LESTE - Sequeira, Ana Teresa (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.10.TAHUN 2017DO - 10.24843/EEB.2017.v06.i10.p03, 2017)
This study aims to know the influence of Reward and Work Motivation toWork Commitment and Performance Volunteer of Community Radio in Timor-Leste. The research was conducted using survey methods to Community Radios’ volunteer and analyzed using path analysis. The population of the research was 105 volunteers of the 16 community radios. The samples of the research consisted of 78 volunteers and were taken by using the proportionate stratified random sampling technique.The results of the research are as follows: (1) there is a significant effect of the reward to the commitment of the volunteers of the Community Radio; (2) there is a significant effect of the work motivation to the commitment of the volunteers of the Community Radio; (3) there is a significant effect of the reward to the work performance of the volunteers of the Community Radio; (4) there is a significant effect of the work motivation to the commitment of the volunteers of the Community Radio; (5) there is a significant effect of the commitment to the work performance of the volunteers of the Community Radio.The result discovers that work motivation more influence then rewards in term of improving staff commitment and work performance